Analisis Survival Parametrik Pada Data Tracer Study Universitas Sriwijaya - Faruk, Alfensi (Jurnal Matematika; Vol 5 No 2 (2015)DO - 10.24843/JMAT.2015.v05.i02.p57, 2015)
In this study, we aimed to (1) show whether the Sriwijaya University tracer study data follow some survival distributions,  (2)  find the best survival distribution to represent the data, and (3) estimate the survival probability and hazard rate of the data. The tracer study was conducted from January 1, 2012 to December 31, 2012. There were 637 alumni who participated in the study. The result showed that the data follow the normal distribution, logistic distribution, and SEV distribution, in which the normal distribution was the best in representing the data. Based on the estimation procedure, the lowest probability of finding the first job was before graduation and the highest probability was about two years after graduation.
Keywords: Parametric Survival Model, Tracer Study, Survival Distribution